Dot and Tot of Merryland - Baum, L. Frank (Lyman Frank), 1856-1919; Denslow, W. W. (William Wallace), 1856-1915 (Salt Lake City, UT : Project Gutenberg, 2011)
"Dot and Tot of Merryland" by L. Frank Baum is a children's novel published in 1901. A young girl named Dot and a little boy named Tot discover a magical land by floating down a river through a tunnel. Merryland contains seven enchanted valleys, each with its own wonders$1 (Bfrom living clowns and candy people to wind-up toys and a mysterious Queen. This whimsical adventure, illustrated by W. W. Denslow, explores a fantastical world that would later connect to Baum's famous Oz series. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dot_and_Tot_of_Merryland
Release date is 2011-11-11
Produced by Michael Gray
Keywords: Fantasy fiction